Effects of propagation method and methyl jasmonate treatment on stem bark wound healing in Norway spruce seedlings - Berggren, Kristina; Tudoran, Amelia; Chen, Yayuan; Tikkinen, Mikko; Bylund, Helena; Björkman, Christer; Egertsdotter, Ulrika; Puentes, Adriana (Springer Nature, 2025)
Healing of stem bark wounds is important for minimizing pathogen infection risk, restoring nutrient transport and structural support in trees. Here, we explore how propagation through somatic embryogenesis (SE) and methyl jasmonate (MeJA) treatment affect wound healing ability in Norway spruce (Picea abies) plants. We inflicted a mechanical wound on the lower stem of MeJA- and non-treated plants produced via SE (emblings) or from seeds (seedlings). Visible signs of healing around the wound edges (onset of healing) were recorded 2 weeks post-wounding; wound size (exposed xylem) was measured every other week (June–September) in year 1, and May and September in year 2. Plant height and diameter were also measured. MeJA positively affected healing onset, with 48% more MeJA- than non-treated plants exhibiting early healing. This resulted in a sharp decrease in wound size for MeJA-treated plants 2–4 weeks post-wounding. However, these benefits only occurred early on, as MeJA reduced the overall healing rate (tissue growth/day) by 9%. For SE, fewer emblings (70%) showed early healing signs compared to seedlings (91%). Yet, non-treated emblings showed the highest healing rate during year 1; in year 2, these effects persisted with all emblings having a 61% faster healing rate and 68% more had completely closed their wounds relative to seedlings. Wounding did not affect growth, MeJA negatively affected diameter but not height, and overall emblings grew less than seedlings. We conclude that MeJA may stimulate stem wound healing initiation in Norway spruce, but slow down healing rate and vice versa for SE plants.
Keywords: emblings; Picea abies; mechanical wounding; plant tolerance; seedlings; somatic embryogenesis; wound healing rate